Focusing on a Needs Analysis on English for Geographic Sciences - Badilla-Ramos, Karina (2023)
A needs analysis was conducted to develop an English for Specific Academic Purposes course for the major Geographic Sciences with emphasis in Land Use Planning at the Universidad Nacional, Costa Rica. This study reports on the needs analysis process and provides a curricular proposal developed for this program. This investigation aims to contribute to field of applied linguistics since little research has been done on needs analysis in English for specific purposes for Geographic Sciences. Most research has focused on methodologies for data gathering and language teaching approaches.